Comparison of Three Different Treatment Modalities in the Management of Cancer Cachexia. Issue 2 (March 2013) - Kanat, Ozkan; Cubukcu, Erdem; Avci, Nilufer; Budak, Ferah; Ercan, Ilker; Canhoroz, Mustafa; Olmez, Fatih
Aims and background: The optimal treatment of cancer cachexia remains unknown. In this study, we compared the efficacy of three different treatment modalities in the management of cancer cachexia. Methods: Sixty-two assessable cachectic cancer patients were randomized to one of the following three arms: 1) megesterol acetate (MA) plus meloxicam (n = 23); 2) MA plus meloxicam plus oral eicosapentaenoic acid (EPA)-enriched nutritional supplement (n = 21); or 3) meloxicam plus oral EPA-enriched nutritional supplement (n = 18). Treatment duration was 3 months. Results: The treatment arms were well balanced at baseline. The primary efficacy (body weight and lean body mass) and secondary efficacy (body mass index, quality of life, and serum levels of IL-6 and TNF-α) parameters improved after treatment in all three arms. There were no statistically significant differences between treatment groups in the mean percentage changes in all efficacy parameters from baseline to end of study. Conclusions: MA plus meloxicam or EPA supplement plus meloxicam may be effective treatment options in the management of cancer cachexia. The combined use of these agents does not provide further advantages.